Constructing and Standardizing Cognitive Test in Artist Competition Rule for Epee Referees - Nagham Khaled Yaseen; Alaa Abdulla Alrawi (College of Physical Education and Sport Sciences, 2021)
The research aimed at constructing and standardizing a cognitive test in competition rules for epee referees as well as identifying the validity of these tests. The problem of the research lies in the lack of cognitive tests made for fencing referees. The researchers used the descriptive method on (50) referees and the pilot study was conducted on (3) while constructing subjects (47) and standardizing subjects were (45). The test was distributed, collected, and treated using proper statistical operations to conclude that there are differences between referees in their level that proves the validity of this test to measure cognitive knowledge of competition rules.